Democracy, governance, and economic performance : theory and evidence - Feng, Yi, 1956- (MIT Press, 2003)
In this book, Yi Feng combines political and economic analyses to study the effects of political institutions on economic performance. Traditionally, political scientists disregard details of economic conditions, while economists may not take into consideration a systematic explanation of political regimes. The growing interest in the interplay of political and economic systems, spurred by the political democratization and economic liberalization evident in many countries over the last twenty years, merits this new perspective. The book examines the political determinants of economic growth, and, specifically, the controversial question of the relationship between democracy and quality of life. Feng systematically studies three variables of a political system--political freedom, political stability, and policy certainty--and relates them to economic development. He examines the political factors that may affect patterns of growth directly or indirectly.Combining theory and country-specific case studies, Democracy, Governance, and Economic Performance demonstrates that political institutions and conditions do matter in economic growth. After establishing a theoretical foundation, Feng tests it by examining the direct effects of the three key political variables on economic growth and the indirect effects of democracy in terms of other variables (political instability, inflation, investment, education, income distribution, property rights, and population growth). He concludes by considering the policy implications of these results.
Keywords: Democracy -- Economic aspects.; Economic development -- Political aspects.; Political science -- Economic aspects.; Démocratie -- Aspect économique.; Développement économique -- Aspect politique.; Institutions politiques -- Aspect économique.; 83.33 economic fluctuations.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Démocratie.; Développement économique.; Institutions politiques.; Croissance économique.; Doctrines économiques.; Democracy -- Economic aspects; Economic development -- Political aspects; Political science -- Economic aspects; Demokratie; Demokratisierung; Liberalisierung; Politische Ökonomie; Politisches System; Wirtschaftsentwicklung; Wirtschaftswachstum; Economische groei.; Politieke aspecten.; Democratie.; Politieke stabiliteit.; Economische aspecten.; Zekerheid.; ECONOMICS/Political Economy